2006
DOI: 10.1124/jpet.105.097642
|View full text |Cite
|
Sign up to set email alerts
|

Diadenosine Polyphosphate Analog Controls Postsynaptic Excitation in CA3-CA1 Synapses via a Nitric Oxide-Dependent Mechanism

Abstract: Previously, we have described the modulatory effect of diadenosine polyphosphates Ap 4 A and Ap 5 A on synaptic transmission in the rat hippocampal slices mediated by presynaptic receptors (Klishin et al., 1994). In contrast, we now describe how nonhydrolyzable Ap 4 A analog diadenosine-5Ј,5ٞ-P 1 ,P 4 -[␤,␤Ј-methylene]tetraphosphate (AppCH 2 ppA) at low micromolar concentrations exerts strong nondesensitizing inhibition of orthodromically evoked field potentials (OFPs) without affecting the amplitude of excita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 78 publications
0
5
0
2
Order By: Relevance
“…AppNHppA and AppCH 2 ppA were prepared using LysU-mediated synthetic–biosynthetic (chemo-enzymatic) procedures as described previously 42,43 with rigorous purification by high-performance liquid chromatography. 44,45…”
Section: Methodsmentioning
confidence: 99%
“…AppNHppA and AppCH 2 ppA were prepared using LysU-mediated synthetic–biosynthetic (chemo-enzymatic) procedures as described previously 42,43 with rigorous purification by high-performance liquid chromatography. 44,45…”
Section: Methodsmentioning
confidence: 99%
“…На відміну від ендогенних ApnAs, синтезовані аналоги можуть бути виготовлені з модифікаціями, які дають змогу уникнути дуже високої гідролізувальної активності різноманітних нуклеаз. Так, аналог діаденозинового поліфосфата, що не гідролізується AppCH2ppA, в якому оксомости було замінено на карбогенові, показав анальгетичні властивості у деяких моделях болю [36]. Нещодавно синтезований аналог, що не гідролізується, з азотним залишком (AppNH2ppA) спричинив пригнічення a,b-meАТФ-індукованого Р2Х3-рецепторопосередкованого струму, діючи саме через процес високоафінної десенситизації.…”
Section: агенти що діють через десенси-тизований р2х3-рецепторunclassified
“…Цей ліганд має невеликий потенціюючий ефект на АТФ-струми, але, що важливо, надзвичайно пригнічує Р2Х3-рецепторопосередковані струми, впливаючи тільки на десенситизований рецептор. Алостеричний механізм дії пуротоксину полягає в уже відомому процесі «замороження» десенситизації за допомогою приєднання до високоафінного сайта зв'язування [22,36,27].…”
Section: агенти що діють через десенси-тизований р2х3-рецепторunclassified
“…For many years there has been an interest in diadenosinepolyphosphates (Ap n A, where n is 2-7), as natural extracellular and intracellular signaling molecules present in the brain (Pintor et al 1993;Baxi and Vishwanatha 1995;Miras-Portugal et al 1999) that can regulate neuronal activity through activation of purinergic P2X and P2Y receptors (Pintor et al 1993(Pintor et al , 1996Lazarowski et al 1995;Pintor and Miras-Portugal 1995;Schachter et al 1996;Wildman et al 1999). We previously showed that a stable analogue of diadenosine-tetraphosphate, known as β, β′-methylene diadenosine 5′,5″′-P 1 , P 4 -tetraphosphate (AppCH 2 ppA) selectively modulates the excitability of hippocampal CA1 pyramidal neurons (Melnik et al 2006). We hypothesized that such a nonhydrolysable compound might exert targeted antiepileptic actions by an adenosine-dependent mechanism.…”
Section: Introductionmentioning
confidence: 99%